Review of Selection Methods in Genetic Algorithms (International Journal of Engineering and Computer Science, 2017)
Genetic Algorithm solves a problem using an evolutionary approach by generating mutations to the current solution method, selecting the better methods from this new generation, and then using these improved methods to repeat the process. Selection is the process of finding out the best individuals for mating process so that the offsprings are produced are fit than the previous population. This paper reviews the commonly used selection methods.